Kraft pulping properties of european black Pine cone - Koray Gulsoy, Sezgin; Ozturk, Fatih (Maderas. Ciencia y Tecnología, 2025)
In this study, different mixtures of cones and wood chips of European black pine (Pinus nigra) were kraft cooked, and the resulting pulp and paper properties were investigated. Also, the chemical compositions and fiber dimensions of the cones and wood were examined. Cone chips were mixed in different ratios (5%, 10%, 15%, and 20%) with wood chips prior to pulping. Also, kraft pulping of 100% cone chips and 100% wood chips were conducted so the results could be compared. The kraft pulp of 100% cone chips had lower pulp yield, lower pulp strength, and higher kappa number than that of 100% wood chips. As the ratio of cone chips was increased in the mixture of cone chips and wood chips, higher kappa numbers and lower total screened yield were obtained. Additionally, the strength properties and brightness of the resulting kraft pulp were decreased gradually. However, the opacity of the pulp was increased slightly. Consequently, cone fibers of European black pine can be used as a raw material in the paper industry by mixing with wood fibers.